2010
DOI: 10.1002/lsm.20935
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐organ biodistribution of gold nanoparticles using intrinsic two‐photon‐induced photoluminescence

Abstract: Background and Objectives-Gold nanoparticles (GNPs) such as gold nanoshells (GNSs) and gold nanorods (GNRs) have been explored in a number of in vitro and in vivo studies as imaging contrast and cancer therapy agents due to their highly desirable spectral and molecular properties. While the organ-level biodistribution of these particles has been reported previously, little is known about the cellular level or intra-organ biodistribution. The objective of this study was to demonstrate the use of intrinsic two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…2,26 In addition, their strong NIR plasmon peak (Figure 1) enables them to scatter, absorb or luminesce when excited in the NIR. 27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared).…”
Section: Discussionmentioning
confidence: 99%
“…2,26 In addition, their strong NIR plasmon peak (Figure 1) enables them to scatter, absorb or luminesce when excited in the NIR. 27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared).…”
Section: Discussionmentioning
confidence: 99%
“…Prior observations in PC-3 and other xenograft models using gadolinium based blood pool contrast agents [41] indicate that the peripheral cortex is more permeable than the tumor core which indicates that passive accumulation of the nanoshells is likely to be higher in these areas. This is in line with our observations on microscopy as well as spatial temperature profiles measured by MRTI.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, gold nanoparticles of 2-10 nm in diameter have low cellular uptake and renal clearance while large particles would be easily opsonized and ineffectively penetrate tumors via extravasation through fenestrations of vessels or by traveling through smaller terminal branches [37][38][39][40]. Pegylated HGNPs used for this study were designed to have average diameters of 52 nm, which has been known to show the highest cellular uptake [41][42][43], resulting in an absorption peak at 810 nm for maximum light penetration into tissue.…”
Section: Hgnp Characterizationmentioning
confidence: 99%